Pemberdayaan Zakat dalam Program Angkringanmu Perspektif in Kind Models Studi LAZISMU Kota Magelang - Putri, Endah Pratika Hasto; Maftuh, Agus Muhammad; Rahayu, Fidaul Lely Puji; Ardianto, Yusuf; Triyanto, Andi (Universitas Siliwangi, 2022)
This article analyzes the empowerment of zakat as a social instrument with implications for alleviating poverty. This study aims to explore the empowerment of zakat in the AngkringanMU program from the perspective of in kind models as well as the economic impact and benefits of zakat on mustahik. This research uses a qualitative approach with the type of case study. The primary data sources used are management bodies, coaches, LAZISMU partners and AngkringanMU customers. Methods of data collection using interviews, observation, and documentation. The instruments used were interview guidelines, observation guidelines, and document scrutiny sheets. The validity of the data used triangulation of sources, time, methods, and the extension of the research time. Data analysis used qualitative analysis with data collection, data reduction, and conclusion. The results of the study reveal that LAZISMU Magelang City has implemented in kind models in terms of empowerment: 1) Production equipment and cash as initial business capital, 2) Monitoring for mustahik, 3) Direct monitoring for mustahik, 4) Giving infaq boxes to mustahik. The AngkringanMU program has an economic impact on mustahik, as follows: 1) Income: partners have a source of income every month, there is a 25% increase in monthly income. 2) Welfare: partners fill in the infaq box, although it is not mandatory. 3) Networking: a discussion forum once a month is a place to share business development strategies. 4) Spirituality: a forum for friendship, making partners more religious and understanding their obligations for the sustenance that is zakat.Keywords: Empowerment; LAZISMU; AngkringanMU; In kind models